2018
DOI: 10.1159/000488389
|View full text |Cite
|
Sign up to set email alerts
|

Rising above It: Status Ambivalence in Older Adults

Abstract: Background: Social status is the standing of a person or group in the social hierarchy, and is perceived to change across the life span from low social status in early life, to peak in midlife, and to a decline thereafter. As threats to subjective social status are known to be detrimental to individuals’ health, it is important to better understand how older adults perceive themselves and others in terms of age-related social status. Objective: We examined status ambivalence – the potential discrepancy between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…Nevertheless, the current findings show that older adults seem to be resilient in the face of status loss in later adulthood . This is consistent with previous research (Robertson & Weiss, 2018;Weiss & Freund, 2012) showing that old people share the perception of status loss for other older people but not for themselves. Moreover, older adults tend to feel individually more similar in their subjective social status to middle-aged adults but less so to older adults.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, the current findings show that older adults seem to be resilient in the face of status loss in later adulthood . This is consistent with previous research (Robertson & Weiss, 2018;Weiss & Freund, 2012) showing that old people share the perception of status loss for other older people but not for themselves. Moreover, older adults tend to feel individually more similar in their subjective social status to middle-aged adults but less so to older adults.…”
Section: Discussionsupporting
confidence: 93%
“…Our rationale for using an age group approach was motivated by research showing that people construct and make sense of their age in terms of social categories (e.g., "teenagers," "young adults," "middle-aged adults," and "older adults"; Weiss & Weiss, 2019). The cut-off that we used in our study to differentiate between middle-aged and older adults (i.e., 40 -64 years for middle-aged adults and 65-84 years for older adults) is most consistent with previous studies (Garstka, Hummert, & Branscombe, 2005;Kunzmann, Richter, & Schmukle, 2013;Lachman, 2004;Robertson & Weiss, 2018;Weiss & Freund, 2012).…”
Section: Age-differential Associations Of Changes In Perceived Social...supporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with the notion of aging as a multidimensional and multidirectional process, older adults have been shown to maintain both positive and negative beliefs about their own aging (Connidis, 1989;Robertson & Weiss, 2018;Steverink, Westerhof, Bode, & Dittmann-Kohli, 2001;Weiss & Kornadt, 2018). Notably, positive and negative beliefs about aging can be couched within the context of a visible marker, such as grip strength, that exhibits or defies images of old age.…”
Section: Beliefs About Agingmentioning
confidence: 79%
“…Studies have found that older age is perceived as connected to a decline in standing in the social hierarchy ( Robertson and Weiss, 2018 ). These attitudes are prevalent in varied fields, including the workplace, regardless of one’s physical state ( Van der Horst and Vickerstaff, 2021 ).…”
Section: Introductionmentioning
confidence: 99%